Курганы у села Самойлово (бассейн Грузского Еланчика, северо-восточное Приазовье) - Швецов, М.Л. (Археологический альманах, 2004)
The author was investigating the recorded barrow burial grounds in 1981. Twenty burial places and one religious building were closely looked at in three partially disturbed embankments. The majority of tombs (16) refer to the Bronze epoch, two - to the early Iron Age and two - to the medieval times.